Pengaruh Penambahan Sari Kunyit (Curcuma domestica Val.) terhadap Karakteristik Minuman Serbuk Instan Daun Belimbing Wuluh (Averrhoa bilimbi L.) - Tirtayani, Luh Yuli; Timur Ina, Putu; Diah Puspawati, Gusti Ayu Kadek (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 11 No 2 (2022): Jurnal ITEPA, 2022)
Herbal plants can be used as nutritious processed food products like instant powder drink products. This study aimed to determine the effect of turmeric juice addition on the characteristics of the starfruit leaves instant powder drink and to determine the proper turmeric juice addition that able to produce the starfruit leaves instant powder drink with the best characteristics. The experimental design used was a completely randomized design (CRD) with the treatment of turmeric juice addition consisting of 5 levels: 0%; 5%; 10%; 15%; 20%. The treatment was repeated 3 times in order to obtain 15 experimental units. The data obtained were analyzed by variance test and if the treatment affected the observed parameters, it was continued with Duncan’s Multiple Range Test (DMRT). The result showed that the adition of turmeric juice had significant effect on moisture content, ash content, solubility time, antioxidant activity, total flavonoid, hedonic test (color, aroma, taste and overall acceptance) and also color scoring test. The additions of 20% turmeric juice in starfruit leaves instant powder drink was the best characteristics with: water content of 4.12%, ash content of 1.11%, solubility time of 49.51 seconds, total flavonoid 19.70 mgQE / 100g powder, antioxidant activity of 80.71% with IC50 was 2884.06 ppm, the color liked with yellow color, the aroma liked, the taste liked, the overall acceptance liked, and scoring test with yellow color.